Peningkatan Hasil Belajar Siswa Pada Materi Pai Menggunakan Model Problem Based Learning di UPTD SDN 05 Taram - Refi Fitria; Syawaluddin Syawaluddin; Deslita Deslita; Maisal Hayani; Amiruddin Amiruddin; Dian Nuraga (LPPI Yayasan Almahmudi bin Dahlan, 2024)
This study aims to improve student learning outcomes in Islamic Religious Education (PAI) subjects at UPTD SD N 05 Taram through the application of the Problem Based Learning (PBL) learning model. The research method used was classroom action research (PTK) which was carried out in four cycles. Each cycle consists of planning, implementation, observation, and reflection stages. The subjects of this study were fourth grade students consisting of 16 students. Data were collected through learning outcome tests, observation sheets, and field notes. The results showed that the application of the PBL model can improve student learning outcomes in PAI material. In the pre-cycle, student learning completeness reached 31%, in the first cycle, there was an increase with learning completeness reaching 48%. In the second cycle, there was an increase with learning completeness reaching 62%, in the third cycle, there was an increase with learning completeness reaching 75% and in the fourth cycle, there was an increase again with learning completeness reaching 100%. Thus, it can be concluded that the Problem Based Learning learning model is effective in improving student learning outcomes in Islamic Religious Education material at UPTD SD N 05 Taram.